Comparison of lateral tail vein and retro-orbital venous sinus as routes of inoculation to study Group B streptococcal systemic infection - Jéssica da Conceição Mendonça; Stephen Lumsdaine; Lindsey R. Burcham (Microbiology Spectrum)
ABSTRACT Murine models are commonly used to understand pathogen and host determinants of systemic infection. While these models have proven beneficial for uncovering bacterial mechanisms required for progression to invasive disease, it can be challenging to draw comparisons across studies as several different routes of infection are standardly used for these experiments. In this study, one of the leading bacterial meningeal pathogens, Streptococcus agalactiae, or Group B Streptococcus (GBS), was used to compare experimental outcomes of two commonly used routes of hematogenous infection, lateral tail vein injection and retro-orbital venous sinus injection. Here we demonstrate that both routes of infection result in systemic disease and the onset of clinical symptoms of infection. We show that retro-orbital venous sinus injection results in an initial increase in bacterial dissemination to the spleen and brain tissue of GBS-infected mice, while an increased bacterial burden was only detected in brain tissues at a later time point. Despite differences in initial dissemination and brain bacterial burden, we found that the route of infection did not significantly impact bacterial burden in the blood, kidney, spleen, heart, and lung tissues at experimental endpoints; and similarly did not impact animal health scores during infection; cytokine and proinflammatory protein abundance in the brain tissue; or overall animal survival. In summary, these findings suggest that both tail vein injection and retro-orbital venous sinus injection are viable models to study Group B streptococcal systemic infection and result in largely similar disease outcomes within our tested parameters.IMPORTANCEStreptococcus agalactiae or Group B Streptococcus (GBS) is the leading cause of invasive disease in neonates and immunocompromised adults and is implicated in severe cases of sepsis, pneumonia, and meningitis. Established murine models of hematogenous systemic infection allow for better understanding and investigation of bacterial dispersion, pathogenesis, meningeal inflammation, and interaction with the host. Here we compared two routes of infection, intravenous lateral tail vein and retro-orbital venous sinus, demonstrating that similar experimental outcomes can be observed, regardless of the route of infection for GBS, specifically. These findings help to reinforce the utility of different systemic infection models and provide insight into comparisons across different established models and how these models can be applied in microbial research.